1980
DOI: 10.1180/minmag.1980.043.330.10
|View full text |Cite
|
Sign up to set email alerts
|

Chemical variation of clinopyroxene phenocrysts from the trachybasaltic lavas of Mount Etna, Sicily

Abstract: SummaryThe chemical variation of clinopyroxene phenocrysts from the trachybasaltic lavas of Etna volcano is described. The phenocrysts show a limited, but distinct trend in chemical variation from calcic-augite in the hawaiites to augite in the benmoreites. The trend of this variation is unusual, being one of Mg-enrichment with differentiation of the magma. Ca shows a steady decrease in the clinopyroxenes from the hawaiites to the benmoreites. Na, however, shows little chemical variation in the pyroxenes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…9c). The Na-Ca inter-sector constancy is in agreement with previous sector zoning studies on Etnean clinopyroxene (Downes, 1974;Duncan and Preston, 1980) and other volcanic systems globally (Hollister and Gancarz, 1971;Ferguson, 1973;Leung, 1974). In contrast, disequilibrium partitioning of Na into Al-Ti-rich sectors has been reported for clinopyroxenes from Aleutian (Brophy et al, 1999) and Hawaiian (Hammer et al, 2016;Welsch et al, 2016) basalts, where sector zoning was related to rapid crystal growth.…”
Section: Clinopyroxene-melt Equilibrium and Thermobarometry On Sectorsupporting
confidence: 91%
See 2 more Smart Citations
“…9c). The Na-Ca inter-sector constancy is in agreement with previous sector zoning studies on Etnean clinopyroxene (Downes, 1974;Duncan and Preston, 1980) and other volcanic systems globally (Hollister and Gancarz, 1971;Ferguson, 1973;Leung, 1974). In contrast, disequilibrium partitioning of Na into Al-Ti-rich sectors has been reported for clinopyroxenes from Aleutian (Brophy et al, 1999) and Hawaiian (Hammer et al, 2016;Welsch et al, 2016) basalts, where sector zoning was related to rapid crystal growth.…”
Section: Clinopyroxene-melt Equilibrium and Thermobarometry On Sectorsupporting
confidence: 91%
“…A recipe for handling sector-zoned crystals Sector zoning has been broadly documented in clinopyroxene from alkali basalts (Hollister and Gancarz, 1971;Ferguson, 1973;Wass, 1973;Leung, 1974;Downes, 1974;Duncan and Preston, 1980;Shimizu, 1981;Hammer et al, 2016;Welsch et al, 2016) and less commonly in tholeiitic systems (Nakamura, 1973;Neave and Putirka, 2017) and arc settings (Arculus, 1973;Brophy et al, 1999). However, the potential kinetic controls on mineral chemistry have undermined the utility of these crystals for the interpretation of magma histories.…”
Section: Implications For the Interpretation Of Magma Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This distribution agrees with that observed in sector zoned clinopyroxenes at Mt. Etna (Downes, 1974;Duncan and Preston, 1980;Ubide et al, 2019) and other volcanic systems world-wide (Hollister and Gancarz, 1971;Ferguson, 1973;Leung, 1974). In a recent study on major and trace element zoning of sector zoned clinopyroxene, Ubide et al (2019) demonstrated that sector zoning is strongly dependent on the charge/size of a given cation and its ability to charge-balance the clinopyroxene structure after incorporation of Al 3+ in tetrahedral substitution for Si 4+ .…”
Section: Dynamic Crystallisation Of Clinopyroxene Megacrystssupporting
confidence: 88%
“…Oscillatory zoning, frequent in Mt. Etna cpx as well as plagioclases (Duncan and Preston 1980;Giacomoni et al 2014), has been attributed to diffusion and nucleation rates and/or to major changes in the physical and/or chemical conditions of the magma. Phemister (1937) first suggested that finer-scale oscillations are manifestations of local disequilibrium, while coarser oscillations arise from extensive chemical or physical changes within the magma body.…”
Section: Magma Feeding Systemmentioning
confidence: 98%